(untitled) - Geula, Erfun (New York, 2017)
McGraw-Hill: Preparation for the GRE Test, 2018 provides up-to-date information on the format of the section-adaptive GRE, including a review of each section, the types of questions asked, and common tricks and traps found on the test. Written by an educator who achieved a perfect score on the GRE, the book introduces a specific approach for each section of the exam and emphasizes the reasoning and analytical skills necessary to succeed on the test. You’ll find valuable practice exercises and strategies to help you build your test-taking confidence.
Keywords: Đại học và Cao đẳng,Universities and colleges; Kỳ thi,Công việc sau đại học,Examinations,Graduate work; Hoa Kỳ,United States